Excluded and Frozen Out: Unauthorised Immigrants' (Non)Access to Care after US Health Care Reform. - Marrow, Helen B.; Joseph, Tiffany D. (Tufts University. Tisch Library., 2016)
Though the Affordable Care Act (ACA) of 2010 extends public and private insurance to 32 million individuals in the USA, it expressly excludes unauthorised adult immigrants from participating in the federally-subsidised state health exchanges and the Medicaid expansion. In this article, we show that the ACA has deepened the 'brightness' of unauthorised immigrants' symbolic and social exclusion within the US health care system via a significant boundary expansion for US citizens and long-term legal immigrants that has no parallel for unauthorised immigrants. As an alternative model, we highlight two subnational jurisdictions—one city/county (San Francisco) and one state (Massachusetts)—to show how they have played more promising roles to reframe and unfreeze this 'frozen-out' population. While we demonstrate commonalities in how San Francisco and Massachusetts have successfully 'blurred' unauthorised immigrants' symbolic exclusion and reduced their barriers to health care at the subnational level, we also highlight their mutual limitations, which signal an ongoing need for federal inclusion currently out of sight. Our findings speak to contemporary debates about whether immigrant incorporation is best achieved at the supranational, national or subnational levels.